2016
DOI: 10.1107/s1600576716016058
|View full text |Cite
|
Sign up to set email alerts
|

CrystalCMP: an easy-to-use tool for fast comparison of molecular packing

Abstract: A new approach is introduced for the comparison of molecular packing and the identification of identical crystal structure motifs. It has been tested on data sets for the solid forms of benzamide, cabergoline and trospium. In this approach, the packing similarity is calculated using a simple formula involving the distances between molecular centres and the relative orientations of molecular entities inside a finite molecular cluster. The approach is independent of the atomic labelling, the unit‐cell parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 45 publications
4
86
0
Order By: Relevance
“…The measure of the extent with whicht wo crystal structures deviate from the perfecto verlapping is defineda st he "packing similarity" (PS). [12] The value of PS, in general,i sn ot limited, but in accord with Ref. [12] the crystalsa re almost identicali fP S < 5.…”
Section: Resultssupporting
confidence: 63%
“…The measure of the extent with whicht wo crystal structures deviate from the perfecto verlapping is defineda st he "packing similarity" (PS). [12] The value of PS, in general,i sn ot limited, but in accord with Ref. [12] the crystalsa re almost identicali fP S < 5.…”
Section: Resultssupporting
confidence: 63%
“…A consequence of such a weighting is the possibility to identify similar molecular packing in two crystal structures, one of which is expanded compared with the other (either because they have been measured at different temperatures or because they crystallize with different solvent molecules of various sizes). This was confirmed in previous work on several selected data sets [see Rohlíček et al (2016)]. However, this method required user interaction and, as a result, the software could not be used to automatically compare large quantities of data.…”
Section: Introductionsupporting
confidence: 74%
“…Detection and evaluation of the precision of the molecular symmetry and using it for calculation of the angle of rotation, as was described previously (Rohlíček et al, 2016), was found to be problematic and unsuitable for automation. For that reason, the angle of rotation was replaced by the calculation of root-mean-square deviation (RMSD) of atomic coordinates after both concerned molecules are shifted to the same origin represented by their centroids (see Fig.…”
Section: Solving the Problem Of Symmetrical Moleculesmentioning
confidence: 99%
See 2 more Smart Citations